Encoding, Reading, and Transforming Information Using Multifluorescent Supramolecular Polymeric Hydrogels. Issue 11 (22nd January 2018) - Ji, Xiaofan; Wu, Ren‐Tsung; Long, Lingliang; Ke, Xian‐Sheng; Guo, Chenxing; Ghang, Yoo‐Jin; Lynch, Vincent M.; Huang, Feihe; Sessler, Jonathan L.
Abstract: Traditional (1D, 2D, and 3D) codes are widely used to provide convenient readouts of encoded information. However, manipulating and transforming the encoded information is typically difficult to achieve. Here, the preparation of three fluorescent (blue, green, and red) hydrogels containing both tetracationic receptor–anion recognition motifs and gel‐specific fluorophores is reported, which may be used as building blocks to construct through physical adhesion fluorescent color 3D codes (Code A, Code B, andCode C ) that may be read out by a smartphone. As a result, parts of the individual gel components that make upCode B can be replaced with other gel building blocks to formCode A via a cut and adhesion approach. A fluorophore responsive to ammonia is further incorporated into one of the hydrogels. This allows the gel block‐derived pattern that makes upCode C to be converted toCode A by chemical means. Therefore, the encoded information produced by patterns of the present hydrogels may be transformed through either physical action or by exposure to a chemical stimulus. Due to the nature of the soft materials involved, the codes can be used as wearable materials. Abstract : The encoded information produced by patterns of three fluorescent (blue, green, and red) hydrogels can be transformed through either physical action (cut and reheal) or by exposure to a chemical stimulus (i.e., ammonia). Due to the nature of the soft materials involved, the codes can be used as wearable materials.